1977
DOI: 10.1104/pp.59.3.395
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Hormone-induced Hyperpolarization of the Oat Coleoptile Transmembrane Potential

Abstract: The effects of the plant growth substances indoleacetic acid (IAA) and fusicoccin on the transmembrane potential of Avena coleoptile cells (at 27-29 C) were studied. Fusicoccin caused hyperpolarization of the membrane potential which started after a lag of less than 20 seconds, and which on average reached -49 my at an external K+ concentration of 1 mm and -75 my at 0.1 mm K+. IAA caused a hyperpolanzation of -25 my starting after a lag of 7 to 8 minutes. These results suggest that fusicoccin and IAA both a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(27 citation statements)
references
References 10 publications
5
22
0
Order By: Relevance
“…2), (2) enhancement of proton extrusion, as compared to IAA-free medium (Fig. 3), and (3) hyperpolarization of the membrane potential (Table 1), are in good agreement with results obtained by other investigators (Cleland et al 1977;Kutschera and Schopfer 1985;Felle et al 1991;Lüthen et al 1990;Rücke et al 1993;Keller and Van Volkenburgh 1996;Burdach 2002, 2007;Kurtyka et al 2011). There is no doubt that plasma membrane hyperpolarization observed in the presence of IAA is a consequence of stimulated proton extrusion through H ?…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…2), (2) enhancement of proton extrusion, as compared to IAA-free medium (Fig. 3), and (3) hyperpolarization of the membrane potential (Table 1), are in good agreement with results obtained by other investigators (Cleland et al 1977;Kutschera and Schopfer 1985;Felle et al 1991;Lüthen et al 1990;Rücke et al 1993;Keller and Van Volkenburgh 1996;Burdach 2002, 2007;Kurtyka et al 2011). There is no doubt that plasma membrane hyperpolarization observed in the presence of IAA is a consequence of stimulated proton extrusion through H ?…”
Section: Discussionsupporting
confidence: 81%
“…There is no doubt that plasma membrane hyperpolarization observed in the presence of IAA is a consequence of stimulated proton extrusion through H ? -ATPase (Cleland et al 1977;Lohse and Hedrich 1992;Rücke et al 1993;Hedrich et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hager et al (2) first proposed that auxin activates a plasma membrane ATPase which functions as a proton pump. Auxin can induce membrane hyperpolarization (13,14) and its action is antagonized by inhibitors of ATP synthesis (8,9,15), observations consistent with the operation of an electrogenicq proton pump that utilizes ATP. However, there is no direct evidence for the participation of an ATPase in auxin-induced acidification.…”
mentioning
confidence: 79%
“…Grahm (7) measured external voltages on coleoptiles using surface electrodes and found that voltage changes following unilateral irradiation occurred after the arrival of auxin at the measured sites. More recently, Cleland et al (3) showed that exogenously applied auxin hyperpolarized oat Since the voltage responses occur within seconds to minutes after irradiation, it is likely that an early consequence of the absorption of phototropically active light is to alter the properties of cell membranes. Since the primary site of auxin activity is also thought to be the cell membrane (3), it is perhaps logical that the interacting processes of photoreception and hormone-induced elongation are coordinated at the membrane level.…”
Section: Resultsmentioning
confidence: 99%